The impact of procedural justice on employee turnover intentions and the role of two mediators - Miriam O'Callaghan (Organization Management Journal (OMJ), 2024)
Purpose - While there is ample discussion in management studies and organizational behavior textbooks about the factors that impact organizational outcomes, such as employee retention, this research is focused on exploring the previously unexplored question of how procedural justice, job characteristics and meaningful work influence employees' intentions to leave their organizations. As such, this study aims to investigate the impact of procedural justice on employees' intentions to leave, both independently and in conjunction with job characteristics and meaningful work as mediators. Design/methodology/approach - This study uses partial least squares structural equation modeling (PLS-SEM) to develop the research model and for hypothesis testing. The path model is assessed using critical model fit indices and measures of goodness of fit. Findings - The results reveal a negative relationship between procedural justice and employees' intentions to leave. This negative relationship persists and is strengthened when both job characteristics and meaningful work act as mediators. Although job characteristics only exerted a significant effect through indirect effects, meaningful work demonstrated a significant negative impact on the intentions to leave through both direct and indirect effects. Originality/value - This study presents a new perspective on employee retention by proposing an original mediation-based path model. Through the testing of eleven hypotheses, the study reveals the intricate relationships between the four constructs examined. The findings provide valuable insights that can serve as a basis for future research in management studies and organizational behavior.
Keywords: 650; Turnover intentions; Intention to leave; Procedural justice; Job characteristics; Meaningful work